Successful school-to-training transitions - can individual goal-striving resources compensate for structural obstacles in the local context? - Theuer, Nele [Verfasser]; Weßling, Katarina [Verfasser] (My University, 2025)
Introduction: While it is well-established that structural obstacles such as low local employment opportunities negatively affect adolescents' school-to-work transitions, the impact of individual agency in relation to these obstacles is understudied. Hence, we focus on the key research question of how adolescents' goal-striving resources-tenacious goal pursuit (TGP) and flexible goal adjustment (FGA)-affect successful transitions from secondary school to vocational education and training (VET) against the backdrop of structural obstacles in the local context. Methods: We measured transition success in terms of a) the start of a VET position, b) concordance between attained and aspired VET position, c) deviance from the aspired position and d) satisfaction with the attained VET position. We examined our research questions in a longitudinal design, using data from the German National Educational Panel Study (NEPS). Our sample consisted of adolescents who graduated in 2012/2016 with the aspiration to start VET (N = 3382; MAge = 16.77; nFemales = 1524). We conducted multiple regression analyses to answer our research questions. Results: We found interaction effects of TGP × FGA on three out of four indicators of transition success. Their direction did not only depend on the outcome variable under examination but also on the structure of the local context: High levels of both TGP and FGA are helpful in favorable contexts-that means when local unemployment is low-but maladaptive when structural obstacles are high. Conclusion: We recommend that support programs for adolescents that aim to enhance goal-striving resources should consider these complex interrelations. (author’s abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; G 1.3.2.2 Übergänge; G 1.3.2 Bildungsverhalten und -verläufe; 370; 300; Jugendlicher; Berufseinmündung; Erste Schwelle; Regionale Faktoren; Bildungsaspirationen; Selbstwirksamkeit